Prospek Pengembangan Ekonomi Berbasis Syariah di Era Globalisasi - Hasan Basri Umar; Ratna Mufida (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2022)
The purpose of this service is to provide education and knowledge about the Prospects of Sharia Economic Development for Muslims around the Nurul Huda Expo Waena Mosque - Jayapura City. The service method used is lectures and surveys with questionnaires. This service was welcomed by the congregation of the Nurul Huda Expo Waena Mosque, this kind of service needs to be provided with assistance and sustainability to add insight into sharia-based economic development in the era of globalization.